PENGARUH METODE DISKUSI TERHADAP HASIL BELAJAR MATA PELAJARAN AQIDAH AKHLAK PESERTA DIDIK KELAS VIII DI MTS HASYIM ASY’ARI BATU - Iza Ferdina Aprilia; Ika Ratih Sulistiani; Bahroin Budiya (VICRATINA, 2022)
This study discusses the effect of the discussion learning method on learning outcomes of the subjects of aqidah morals of class VIII students at MTs Hasyim Asy'ari Batu. The background of this research is to apply active and effective learning methods. The research method used is a quantitative research method using a quasi-experimental design method. Data collection techniques used are tests and documentation. The results of this study were the posttest average of the experimental class (81.00) and the average posttest value of the control class (43.33). Then where in the hypothesis test obtained a significant t-test value of 5% obtained tcount > ttable (8.584 > 0.3610). So it can be concluded that there is an influence of the discussion method on the learning outcomes of aqidah morals of class VIII MTs Hasyim Asy'ari Batu.